But I read it on the internet! - Buzzeo, Toni; Yoshikawa, Sachiko (Madison, WI : Upstart Books, 2013)
In this fourth Mrs. Skorupski tale, the librarian with the finest accessories in all of Liberty School shows students how to decide when the Internet is reliable. With the help of the Website Evaluation Gizmo, Hunter discovers that the Internet can provide true facts, Carmen learns that not everything there is true, and together they solve the question of George Washington's teeth.
"A Mrs. Skorupski story"--Cover.
Keywords: Libraries -- Juvenile fiction; Internet -- Safety measures -- Juvenile fiction; Picture books